Alternatif Pemanfaatan Pupuk Organik Dan Pestisida Nabati Bumiku Sehat Dalam Menciptakan Perbaikan Lingkungan Berkelanjutan Dan Potensi Usaha - Berliyan, Berliyan; Al Tabrany, Bryan Topaz; Tricana, Deny Wahyu (Jurnal Abdimas Multidisiplin, 2024)
The majority of the population in Mrayan Village work as farmers, with the main commodities being empon-empon, porang and various vegetables. However, most of the agricultural land in Mrayan Village is still managed using conventional methods, where the use of chemical fertilizers and synthetic pesticides is still very dominant. Management using conventional methods is carried out continuously which results in damage to soil fertility and pollutes the environment in Mrayan Village. In order to empower local potential and overcome environmental problems in Mrayan Village, the Muhammadiyah University of Ponorogo Community Service Team tried to initiate an organic fertilizer product made from goat manure and plant-based pesticides, called "My Healthy Earth". This program collaborates with Mrayan Trigona Park and the Forest Farmer Group as institutions that will manage the product. The research methods used are Diffusion of Science and Technology (IPTEK) and Practical Activity Training. This program not only aims to reduce negative impacts on the environment, but also to create new business opportunities that can improve the local economy. In addition, this organic fertilizer is expected to be traded not only in Mrayan Village but also outside the area.